2008
DOI: 10.1152/ajprenal.90344.2008
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial expression of neuropilins and VEGF receptors in control and interstitial cystitis patients

Abstract: Interstitial cystitis (IC) is a chronic and painful bladder syndrome of unknown cause with no reliable biological marker or effective therapy. Vascular endothelial growth factor (VEGF), which plays a key role in bladder inflammation, is closely associated with the vascular alterations observed in patients with IC. However, our recent findings of VEGF receptors (VEGF-Rs) and VEGF coreceptors on nonendothelial cells in human and mouse urothelium suggest that additional VEGF targets and functions are possible in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 54 publications
4
42
0
Order By: Relevance
“…Previous studies have demonstrated that animal models of urinary bladder inflammation and BPS/IC regulate the VEGF-VEGF receptor system in the urothelium (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). Increased expression of VEGF and receptors has been reported in bladder biopsies from women with BPS/IC and expression of VEGF correlates with pain described by patients (Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that animal models of urinary bladder inflammation and BPS/IC regulate the VEGF-VEGF receptor system in the urothelium (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). Increased expression of VEGF and receptors has been reported in bladder biopsies from women with BPS/IC and expression of VEGF correlates with pain described by patients (Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…9). The uroepithelium detects these sensory stimuli by expressing a large number of surface receptors and ion channels, including EGF family ErbB1-3 receptors (15,209), A 1 , A 2a , A 2b , and A 3 receptors (235), ␣-and ␤-adrenergic receptors (20,26), bradykinin receptors (41), cannabinoid receptors (74,220), fractalkine receptor (236), neurokinin receptor (49), nicotinic and muscarinic receptors (M 1 -M 5 ) (18,22,40,77,121), purinergic P2X 1 , P2X 2 , P2X 3 , P2X 4 , P2X 5 , P2X 6 , P2X 7 , P2Y 1, P2Y 2 , and P2Y 4 receptors (27,58,129,197,200,218,225), protease-activated receptors (47), VEGF receptor/neuropilins (39,176), acid-sensitive ion channels (14,122), ENaC (61,134,224), the NSCC (223,234), TRAAK (234), TREK-1 (234), and the TRP family channels TRPV1, TRPV2, TRPV4, and TRPM8 (21,22,25,33,193) (Fig. 9).…”
Section: Sensory and Effector Functions Of The Uroepithelium: Uroepitmentioning
confidence: 99%
“…Several important proteins associated with bladder inflammation were also investigated as biomarkers for the diagnosis of BPS/IC. Additionally, glomerulations during cystoscopic hydrodistention is highly associated with overexpression of angiogenic growth factors, such as platelet-derived endothelial cell growth factor/thymidine phosphorylase, 65 vascular endothelial growth factor 66 and hypoxia-inducible factor-1-alpha. 67 Measuring the urine concentrations of these angiogenic growth factors could be a new and useful method for the diagnosis of BPS/IC.…”
Section: Urinary Nerve Growth Factor and Inflammatory Markersmentioning
confidence: 99%